SUPERVISION OF CIVIL SOCIETY IN THE IMPLEMENTATION OF GOVERNMENT VILLAGE kakara B - Romony, Kari Hendrik; Rorong, Arie Junus; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRAK: The village is a social institution that was passed on from generation to generation by the people. the new order of government is concerned homogenize the internal order of the village is so diverse in this country. The government wants the village as an instrument of development of effective and efficient. With the Law No. 6 of 2014 on the village, the village returned as part of the right of people, so the presence of village autonomy, which the village organize independently of government. From this, the village was given the authority to regulate and manage their own household and are expected to manage the potential that exists in villages both in the field of human resources, and natural resources, to find out the surveillance society in the implementation of governmental tasks, the researchers malakukan direct research with the number of informants as many as 14 people.Supervision is very important in a government, to encourage and anticipate deviations will occur. In this study informant revealed that the villagers have not been up correcting the results of the work done by the village government, it is because the government never set up a room for deliberation, so that what is done by the village government in particular on the budget the village fund managed by the government does not know then how the budget has been realized by building rural infrastructure, and the rest of the village community fund budget management never know, because the government is not accountable for the village community. In other words, the government should better evaluate the performance and the need to implement corrective actions so that the results of the work in accordance with the plan.Â  Keywords: Society Oversight of Government Management In Village